(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this work, we extend and generalize, the concept of α-Ψ contraction mappings in the setting of b-gauge spaces, where a new aspect of extension has been added . Subsequently, we give some related fixed point results that generalize many existing ones in the literature on this topic. Some of their applications to nonlinear integral equations on unbounded domains, including fractional differential equations with maxima, are also presented.